Regards sur le Mozambique contemporain - Fabrice Folio (EchoGéo)
The aim of this article is to draw out the geographical broad lines of the republic of Mozambique. The country’s spatial organisation is part of the present mutations as well as its complex heritages. Different scales will be considered. Moreover, we will point out both the historical and geographical background. The paper will try to demonstrate that lots of outer stakes as well as external actors have played a major role on the spatial reality of Mozambique. The contemporaneous spatial and socio-economical realities can attest to this point, such as the specific physiognomy of this territory or the gap between national growth and social development. Finally, the spatial Mozambican singularities display several internal “corridors” connected to foreign countries, the localisation of the capital-city, Maputo, at the extreme south periphery of the country and new strategic areas linked to globalisation. The social and spatial coherence of the latter will be issued.